Illiberal venezuelan revolution and its foreign policy (2013)
The "Bolivarian Revolution" (or "chavismo") is the process and political regime led by Hugo Chavez in Venezuela since 1998. This article argues that the political phenomenon can be understood as a case of "totalitarian democracy"(Talmon) or "illiberal"(Zakaria). Both concepts refer to forms of democracy that are related to political messianism, populism and other forms of semi-autocratic leader, apparently favoring a majority will, but acting to the detriment of the rule of law, constitutionalism, the system of individual freedoms and the division of powers. It is further argued that, given the revolutionary nature of Chavez´s foreign policy, this way of understanding and practice of democracy has been exerting a growing influence in Latin America.